Cyber Violence against Women and Girls in Nepal - Kaphle, Poonam (Kathmandu School of Law Review, 2019)
Violence against women and girls in the virtual space is the emerging concern in the global context. With the growth in use of technologies and the internet, cyberspace has been an equally vulnerable area for violence targeted against women and girls as that of public space. With the rise in numbers of existing forms of violence, conceptual clarification on the dynamics of cyber based violence is a major need of time. Moreover, it has been an issue of immediate concern to assess the current situation of Nepal for the identification of policy and legal remedies. The present study attempts to identify the pattern and forms of cyber based violence against women and girls in Nepal through the study of registered cases in Cyber Crime Unit of Nepal Police and also, reflect on the nature of cases adjudicated by the Kathmandu District Court. In the absence of a clear legal framework and technical knowhow of cyber based crimes, law enforcement authorities have been constantly facing challenges to critically intervene the process and secure safe spaces for women and girls in use of technology. The study concludes that a coherent approach from all concerned stakeholders is required in defining a clear legal and policy framework to ensure use of information and technology as a tool of gender empowerment, thus addressing the crimes committed through cyberspace.